Identification of a 42‐bp heart‐specific enhancer of the notch1b gene in zebrafish embryos. Issue 6 (11th April 2019) - Wang, Feng; Yang, Qian; Wu, Fang; Zhang, Yawen; Sun, Shuna; Wang, Xu; Gui, Yonghao; Li, Qiang
Abstract: Background: NOTCH1 plays a key role in the differentiation of ventricles, and mutations are strongly associated with both sporadic and familial bicuspid aortic valves. However, few heart‐specific enhancers have been identified to date. Results: In this study, we investigated evolutionary conserved regions (ECRs) that might act as potential enhancers within the region approximately 150‐kb upstream and downstream of the NOTCH1 gene. Functional validation revealed that one 127‐bp ECR located 85‐kb downstream of the NOTCH1 gene drives green fluorescent protein expression in the zebrafish embryo heart. Transcription factor (TF) prediction and core TF distribution analyses were performed to identify the core region. Dissection of ECR3 was performed to identify the 42‐bp sequence, which is sufficient for heart‐specific expression. In situ hybridization experiments showed that notch1b is expressed in the heart. Overexpression experiments in cells indicated that NKX2‐5 is critical for enhancer activity. Mutation of the NKX‐5 binding site significantly decreased reporter gene expression. Next, compared with the commonly used myocardium‐labeled zebrafish transgenic strain Tg (cmlc2: mCherry), this 42‐bp enhancer‐labeled stable line mediated a similar expression pattern but with a smaller core region. Conclusion: This study identified a 42‐bp heart‐specific enhancer near the NOTCH1 gene and further verified its functional targeting by NKX2‐5. Key Findings: Identification of heart‐specific enhancer of NOTCH1 . A 42‐bp conserved region is required for enhancer activity of the 127‐bp sequence. This 42‐bp enhancer requires a NKX2‐5 binding site.